Uruguay - Corporate Governance Country Assessment - World Bank (Washington, DC, 2013)
This report provides an assessment of Uruguay's corporate governance policy framework, enforcement and compliance practices. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Uruguay. The report identifies several key next steps that focus on implementation including: Improving corporate information, particularly ownership disclosure, related party transactions procedures, and financial reporting; promoting effective and active boards of directors; strengthening institutions, including the securities regulator, and the companies registry; and modernizing securities markets by strengthening intermediation and related regulations.